2015
DOI: 10.4314/ahs.v14i4.36
|View full text |Cite
|
Sign up to set email alerts
|

Health seeking behaviour and challenges in utilising health facilities in Wakiso district, Uganda

Abstract: Background: The health seeking behaviour of a community determines how they use health services. Utilisation of health facilities can be influenced by the cost of services, distance to health facilities, cultural beliefs, level of education and health facility inadequacies such as stock-out of drugs. Objectives: To assess the health seeking practices and challenges in utilising health facilities in a rural community in Wakiso district, Uganda. Methods: The study was a cross sectional survey that used a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
132
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(159 citation statements)
references
References 35 publications
13
132
4
Order By: Relevance
“…3,18,25,26 Various researches have concluded that distance from medical facility greatly influence health seeking behaviour and in turn drug adherence. 27 Cost of Medication and Type of Medical facility didn't show any significance in our study which can be because of free and adequate medications provided by our centre.…”
Section: Discussionmentioning
confidence: 67%
“…3,18,25,26 Various researches have concluded that distance from medical facility greatly influence health seeking behaviour and in turn drug adherence. 27 Cost of Medication and Type of Medical facility didn't show any significance in our study which can be because of free and adequate medications provided by our centre.…”
Section: Discussionmentioning
confidence: 67%
“…According to research from Maneze, et.al., 2015 [33], change in health seeking behavior is effective and sustainable in reducing risk factors for lifestyle diseases. Another research from Derose, Escarce, & Lurie, 2007 [34] and Musoke, 2014 [3] discovers that health seeking behavior are relate to the health outcomes. In line with those research, a research from Abidin, et al, 2014 [35] found that health seeking behavior can prevent the complication of the chronic disease and also enhance the awareness in prevention program for communicable disease [36].…”
Section: Consequencesmentioning
confidence: 99%
“…The concept of health seeking behavior has been used widely as a framework in health care system. Many articles or journals has mentioned it as an action which an individual makes a decision making to find a support to complete his/her personal need that is related to illness condition [2][3][4]. Health seeking behavior concept is related to the role of the nurse in nursing metaparadigm which is to enhance the health potential among individuals by influencing them to make a change in their behavior that can lead to the optimum wellness [5].…”
Section: Introductionmentioning
confidence: 99%
“…33 Next we have studies on toxicology 34 , evaluation of glomerular function 35 , multiple correspondence analysis 36 , and challenges with health seeking. 37 Ding has written for us a very unique paper on virtual plant modelling based on the L-system. 38 Fournier's gangrene is back in the news.…”
mentioning
confidence: 99%